Analysis of beam wander effect in high turbulence for FSO communication link. Issue 20 (23rd October 2018) - Mukherjee, Arka; Kar, Subrat; Kumar Jain, Virander
Abstract : Atmospheric turbulence causes severe impairment of FSO communication link. Existing model underestimates the beam wander effect in high turbulence regime. In this paper, we model each turbulent eddy as a thin dielectric lens with Gaussian shaped refractive index profile and assume there are several sheets of eddies throughout the propagation path. We consider uniformly distributed eddy positions in a laminar sheet with Gamma distributed eddy sizes and refractive index fluctuations. We calculate mean beam wander and link availability for a given aperture size in high turbulence regime. Our simulation results show good concordance with the analytical results.